Il était une fois un arbre... À propos de A árvore das palavras [L'arbre à paroles] de Teolinda Gersão - Marinho, Maria de Fátima (2020)
The novel by Teolinda Gersão, a Portuguese writer from the second half of the 20th century, plays with ambiguous notions that can be associated with the term tree. Knowing that the tree that we see in the landscape and that we study in botany does not exhaust all the meanings inherent in the concept, the author takes pleasure in taking advantage of all the hidden senses and all the cultural symbols that may be present. The seemingly simple novel becomes more and more complex as the tree assumes great importance in the plot. The characters, in absolute loss, intermingle with the landscape and continue to identify the trees with the avatars and the problems of their existence. The former Portuguese colony, Mozambique, is the scene where events take place and where characters more or less adapted to African life clash.